Neenakosti starih ljudi v sodobnih zahodnih družbah kot predmet socialne gerontologije - Štebe, Katarina (Družboslovne razprave, 2014)
The purpose of the article is to give an overview of the theoretical development in social gerontology. In the interdisciplinary field of different paradigms, the most recent bring to the fore the heterogeneity of ageing and therefore the issues of solidarity and social inequality. Through our analysis of established explanations of the social aspects of ageing we expose the role of the theoretical perspectives developed in sociology for understanding the diversity of old age and the experiences of it. The main focus is on questions of social inequality in the modern welfare state, which in recent times has been responding to the challenges of an ageing population with a policy of active (productive) ageing. In seeking to answer these questions at the macro level, the most recent critical gerontology exposes the fact that the diversity of old people is tied to issues of social justice. In a field that sees itself as an advocate for old people in ageing post-industrial societies, this critical strand is accumulating knowledge that helps empower this social group and supports even marginal social groups in these populations in achieving a quality life in old age.
Keywords: Social gerontology; Socialna gerontologija; Staranje; Aging; Družbena neenakost; Social inequality; Država blaginje; Welfare state; stari ljudje; gerontologija